Degree of corrosion and other deterioration effects in highway bridge deck component using non-destructive self potential and vibration testing: case study from SW Nigeria - O. O. Falowo; O. Makinde; Y. Akindureni (Discover Civil Engineering)
Abstract Recently, the corrosion of steel reinforcement and high vibration intensity have become a major problem in highway bridge stability analysis, and structures that involved reinforcing steel. Therefore, based on suspected human perception, the Ogbese highway bridge stability was investigated using non-destructive half-cell method and vibration measurement. The half-cell measurement was taken at 1 × 1 m grid using Cu/CuSO4 half-cell standard reference electrode, while vibration measurement was taken using vibration meter. The meter is capable of switching acceleration measurement between high (1–4 kHz) and low frequency (10 Hz to 1 kHz) with measurement accuracy of ± 10. The SP result showed that areas with Ecorr greater than −200 mV is 90.8%, Ecorr of −350 mV ≤ Ecorr ≤ −200 mV accounts for 8.5%, and areas with Ecorr less than −350 represents 0.7%. Consequently, the bridge deck is still safe at present. The anomalous zones are represented in each of the bridge span, and mostly within the location of the piers. This implies that there are contributions from the piers/piles reinforcements’ activity. The bridge is also characterized by varying vibration intensity, very high at the northeastern part in terms of acceleration, and displacement than at the southwestern, and middle parts. This is also supported by comparative wide range of values obtained at northeastern part—acceleration, and displacement for the vibration intensities. However, the increasing corrosion activity presently going on may undermine its stability in the long run. Hence a need for thorough maintenance and assessment from time to time.